Interview with Debabrata Banarjee, state committee member of RSP of WB (India) on communist and trade union movement. Interviewed by Kabir - Kabir, Shahriar.
Interview with Debabrata Banarjee, state committee member of RSP of WB (India) on communist and trade union movement. Interviewed by Kabir.